Morphological Degradation of Oxygen Evolution Reaction-Electrocatalyzing Nickel Selenides at Industrially Relevant Current Densities - Hiege, Felix; Chang, Chun-Wai; Trost, Oliver; van Halteren, Charlotte E. R.; Hosseini, Pouya; Bendt, Georg; Schulz, Stephan; Feng, Zhenxing; Linnemann, Julia; Tschulik, Kristina (ACS Applied Materials & Interfaces)
We investigated electrodeposited nanoparticulate nickel selenide (pre)catalysts that transform into nickel oxides/oxyhydroxides under oxygen evolution reaction conditions in alkaline solutions. Previous studies of this transformation were conducted at lower current densities than those of industrial relevance (≥1 A cm–2). We used ultramicroelectrodes (UMEs) to achieve such current densities, benefiting from their small size, ensuring low absolute currents and low ohmic drop but high current densities. Morphological degradation of the catalyst material was only observed at current densities exceeding 1 A cm–2 but not for smaller ones. Using X-ray absorption, X-ray photoemission spectroscopy, and X-ray diffraction, we confirmed that the degradation was accompanied by the literature-known transformation of nanoparticulate Ni3Se2 (bulk)/NiSe (surface) into nickel oxyhydroxide. The transformation of the precatalyst goes along with a significant improvement in the charge transfer kinetics observed by decreasing Tafel slopes with ongoing experimental time extracted from cyclic voltammetry (CV) experiments and electrochemical impedance spectroscopy (EIS) in the high-frequency range. However, these kinetic improvements are accompanied by limitations in mass transport concluded from decreasing current responses at high overpotentials in CVs and increasing impedance in the low-frequency range of the EIS spectra after extended CV cycling. These mass transport limitations originated from morphological degradations at the UME exceeding 1 A cm–2 which we proved by applying identical location scanning electron microscopy. This has not been reported in studies that have been limited to lower current densities before. Our findings showcase how UMEs can be used to study (pre)catalysts (herein nickel selenides) under current densities of industrial relevance in the absence of ohmic drop-related ambiguities, combined with in-depth materials characterization studies, e.g., identical location microscopy and advanced spectroscopic methods. This approach enables direct evaluation and comparison of catalyst materials and thus demonstrates how to overcome long-standing limitations of electrocatalyst design and testing.
Keywords: Electrocatalysis; oxygen evolution reaction; nickel selenide; microelectrode

Overcoming the Miscibility Gap of GaN/InN in MBE Growth of Cubic InxGa1–xN - Zscherp, Mario Fabian; Jentsch, Silas Aurel; Müller, Marius Johannes; Lider, Vitalii; Becker, Celina; Chen, Limei; Littmann, Mario; Meier, Falco; Beyer, Andreas; Hofmann, Detlev Michael; As, Donat Josef; Klar, Peter Jens; et al. (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Surface Passivation and Detrimental Heat-Induced Diffusion Effects in RbF-Treated Cu(In,Ga)Se2 Solar Cell Absorbers - Elizabeth, Amala; Sahoo, Sudhir K.; Phirke, Himanshu; Kodalle, Tim; Kühne, Thomas; Audinot, Jean-Nicolas; Wirtz, Tom; Redinger, Alex; Kaufmann, Christian A.; Mirhosseini, Hossein; Mönig, Harry (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

P-Terminated InP (001) Surfaces: Surface Band Bending and Reactivity to Water - Moritz, Dominik Christian; Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Frieß, Tilo; Runge, Erich; Hofmann, Jan P.; Hannappel, Thomas; Schmidt, Wolf Gero; Jaegermann, Wolfram (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Oligothiophene Phosphonic Acids for Self-Assembled Monolayer Field-Effect Transistors - Zhao, Baolin; Gothe, Bastian; Groh, Arthur; Schmaltz, Thomas; Will, Johannes; Steinrück, Hans-Georg; Unruh, Tobias; Mecking, Stefan; Halik, Marcus (ACS Applied Materials & Interfaces)

Caffeine-Derived Noble Carbons as Ball Milling-Resistant Cathode Materials for Lithium-Ion Capacitors - Ilic, Ivan K.; Lepre, Enrico; Lopez Salas, Nieves (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Dually Crosslinked Supramolecular Hydrogel for Cancer Biomarker Sensing - Li, Jie; Ji, Chendong; Lü, Baozhong; Rodin, Maksim; Paradies, Jan; Yin, Meizhen; Kuckling, Dirk (ACS Applied Materials & Interfaces)

Dually Crosslinked Supramolecular Hydrogel for Cancer Biomarker Sensing - Li, Jie; Ji, Chendong; Lü, Baozhong; Rodin, Maksim; Paradies, Jan; Yin, Meizhen; Kuckling, Dirk (ACS Applied Materials & Interfaces)

Cellulose Nanocrystal-Templated Tin Dioxide Thin Films for Gas Sensing - Ivanova, Alesja; Frka-Petesic, Bruno; Paul, Andrej; Wagner, Thorsten; Jumabekov, Askhat N.; Vilk, Yury; Weber, Johannes; Schmedt auf der Günne, Jörn; Vignolini, Silvia; Tiemann, Michael; Fattakhova-Rohlfing, Dina; Bein, Thomas (ACS Applied Materials & Interfaces)
Porous tin dioxide is an important low-cost semiconductor applied in electronics, gas sensors, and biosensors. Here, we present a versatile template-assisted synthesis of nanostructured tin dioxide thin films using cellulose nanocrystals (CNCs). We demonstrate that the structural features of CNC-templated tin dioxide films strongly depend on the precursor composition. The precursor properties were studied by using low-temperature nuclear magnetic resonance spectroscopy of tin tetrachloride in solution. We demonstrate that it is possible to optimize the precursor conditions to obtain homogeneous precursor mixtures and therefore highly porous thin films with pore dimensions in the range of 10–20 nm (ABET = 46–64 m2 g–1, measured on powder). Finally, by exploiting the high surface area of the material, we developed a resistive gas sensor based on CNC-templated tin dioxide. The sensor shows high sensitivity to carbon monoxide (CO) in ppm concentrations and low cross-sensitivity to humidity. Most importantly, the sensing kinetics are remarkably fast; both the response to the analyte gas and the signal decay after gas exposure occur within a few seconds, faster than in standard SnO2-based CO sensors. This is attributed to the high gas accessibility of the very thin porous film.

Low-Temperature Plasma-Enhanced Atomic Layer Deposition of Tin(IV) Oxide from a Functionalized Alkyl Precursor: Fabrication and Evaluation of SnO2-Based Thin-Film Transistor Devices - Mai, Lukas; Zanders, David; Subaşı, Ersoy; Ciftyurek, Engin; Hoppe, Christian; Rogalla, Detlef; Gilbert, Wolfram; Arcos, Teresa de los; Schierbaum, Klaus; Grundmeier, Guido; Bock, Claudia; Devi, Anjana (ACS Applied Materials & Interfaces)

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas; Mirhosseini, S. Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

Low-Temperature Plasma-Enhanced Atomic Layer Deposition of Tin(IV) Oxide from a Functionalized Alkyl Precursor: Fabrication and Evaluation of SnO2-Based Thin-Film Transistor Devices - Mai, Lukas; Zanders, David; Subaşı, Ersoy; Ciftyurek, Engin; Hoppe, Christian; Rogalla, Detlef; Gilbert, Wolfram; de los Arcos de Pedro, Maria Teresa; Schierbaum, Klaus; Grundmeier, Guido; Bock, Claudia; Devi, Anjana (ACS Applied Materials & Interfaces)

Novel ALD Chemistry Enabled Low-Temperature Synthesis of Lithium Fluoride Coatings for Durable Lithium Anodes - Chen, Lin; Chen, Kan-Sheng; Chen, Xinjie; Ramirez, Giovanni; Huang, Zhennan; Geise, Natalie R.; Steinrück, Hans-Georg; Fisher, Brandon L.; Shahbazian-Yassar, Reza; Toney, Michael F.; Hersam, Mark C.; Elam, Jeffrey W. (ACS Applied Materials & Interfaces)

Dynamics of DNA Origami Lattice Formation at Solid–Liquid Interfaces - Kielar, Charlotte; Ramakrishnan, Saminathan; Fricke, Sebastian; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

PEALD of SiO2 and Al2O3 Thin Films on Polypropylene: Investigations of the Film Growth at the Interface, Stress, and Gas Barrier Properties of Dyads - Gebhard, Maximilian; Mai, Lukas; Banko, Lars; Mitschker, Felix; Hoppe, Christian; Jaritz, Montgomery; Kirchheim, Dennis; Zekorn, Christoph; de los Arcos de Pedro, Maria Teresa; Grochla, Dario; Dahlmann, Rainer; Grundmeier, Guido; et al. (ACS Applied Materials & Interfaces)

PEALD of SiO2 and Al2O3 Thin Films on Polypropylene: Investigations of the Film Growth at the Interface, Stress, and Gas Barrier Properties of Dyads - Gebhard, Maximilian; Mai, Lukas; Banko, Lars; Mitschker, Felix; Hoppe, Christian; Jaritz, Montgomery; Kirchheim, Dennis; Zekorn, Christoph; de los Arcos de Pedro, Maria Teresa; Grochla, Dario; Dahlmann, Rainer; Grundmeier, Guido; et al. (ACS Applied Materials & Interfaces)

PEALD of SiO2 and Al2O3 Thin Films on Polypropylene: Investigations of the Film Growth at the Interface, Stress, and Gas Barrier Properties of Dyads - Gebhard, Maximilian; Mai, Lukas; Banko, Lars; Mitschker, Felix; Hoppe, Christian; Jaritz, Montgomery; Kirchheim, Dennis; Zekorn, Christoph; de los Arcos de Pedro, Maria Teresa; Grochla, Dario; Dahlmann, Rainer; Grundmeier, Guido; et al. (ACS Applied Materials & Interfaces)

Strain Compensation in Single ZnSe/CdSe Quantum Wells: Analytical Model and Experimental Evidence - Rieger, Torsten; Riedl, Thomas; Neumann, Elmar; Grützmacher, Detlev; Lindner, Jörg; Pawlis, Alexander (ACS Applied Materials & Interfaces)

Threshold Switching Induced by Controllable Fragmentation in Silver Nanowire Networks - Wan, Tao; Pan, Ying; Du, Haiwei; Qu, Bo; Yi, Jiabao; Chu, Dewei (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Regular Nanoscale Protein Patterns via Directed Adsorption through Self-Assembled DNA Origami Masks - Ramakrishnan, Saminathan; Subramaniam, Sivaraman; Stewart, A. Francis; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)